The Impacts of Rip Curl Pro, Surf Competition, in Peniche (Portugal) - Nunes, Rosa (2018)
Deeply connected to the sea, its greatest resource, Peniche, from its early development has become over the years one of the main references in nautical tourism, with surf being its main sport practice. In fact, nowadays, surf is the main source of income of the municipality. The popularity of this destination as a standard for nautical sports has gained such a dimension that has attracted the attention of one of the world’s leading nautical sports events, the Rip Curl Pro. Since 2009 (the first time this event took place in that city) to the present day, the impacts of this event have not been only felt in the Western region but also throughout the country.